CHERRY LAUREL (PRUNUS LAUROCERASUS) EXTRACT AND LİPOSOME ENCAPSULATION - Esma Nur BULUT; Can Ali AĞCA; Nilgün ERTAŞ (Biotechnologia Acta, 2025)
Aim. The study aimed to determine the antioxidant activity and the number of phenolic substances of cherry laurel fruit and to reveal the usability of the fruit for other studies.